Pocong Oath Law in Palembang City - Randi, Randi; Hendarso, Yoyok; Purnama, Dadang Hikmah; Arianti, Yosi (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
This research was motivated by the phenomenon of the pocong oath carried out by Lorong A Rahman Residents, RT 10/04, Kelurahan 1 Ilir, Ilir Timur II District Palembang City, which had shocked the public on social media. Besides that, this issue often occurs in the community. The pocong oath is closely related to shari'áh. The pocong oath is substantially the same as a cultural practice or a community custom; it is done when there is a dispute or problem of a mystical nature or to prove something. Rationality is essential to distinguish between the truth of belief and rationality, which refers to the basis for believing it. The findings of this study are that the religious point of view related to the pocong oath is that there must be a name of God and that it is a truth. The method used in this study is qualitative research with three data collection techniques, namely in-depth interviews, conservation and documentation.